1989
DOI: 10.1073/pnas.86.14.5557
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HLA-A,B,C allele products and lymphocyte function-associated antigen 3 in colorectal neoplasia.

Abstract: The expression of HLA-A,B,C antigens and lymphocyte function-associated antigen 3 in human colorectal adenomas and adenocarcinomas was studied by immunohistochemistry. None of 10 adenomas and only 1 of 30 carcinomas had lost expression of all HLA-A,B,C molecules. On the other hand, focal loss of an HLA-B product was seen in 2 of the adenomas, and complete losses of tumor cell HLA-A2 (in 7 of 13 cases), HLA-Bw4 (in 4 of 13 cases), and HLA-A3 (in 1 of 6 cases) were seen in the carcinomas. No complete losses of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
46
2

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 30 publications
(24 reference statements)
9
46
2
Order By: Relevance
“…Our observed frequency of alterations in HLA-I is in agreement with other studies and suggests that our study cohort is comparable with other reported populations (Cordon et al, 1991;Durrant et al, 1987;Kaklamanis et al, 1992;Lopez-Nevot et al, 1989;Moller et al, 1991aMoller et al, , 1991bMoore et al, 1986;Smith et al, 1989;Stein et al, 1988;van den Ingh et al, 1987). The improved prognosis for patients with tumors that had down-regulated HLA-I, and HLA-A in particular, is a novel finding and argues against the importance of T-cell-mediated immune surveillance.…”
Section: Discussionsupporting
confidence: 82%
“…Our observed frequency of alterations in HLA-I is in agreement with other studies and suggests that our study cohort is comparable with other reported populations (Cordon et al, 1991;Durrant et al, 1987;Kaklamanis et al, 1992;Lopez-Nevot et al, 1989;Moller et al, 1991aMoller et al, , 1991bMoore et al, 1986;Smith et al, 1989;Stein et al, 1988;van den Ingh et al, 1987). The improved prognosis for patients with tumors that had down-regulated HLA-I, and HLA-A in particular, is a novel finding and argues against the importance of T-cell-mediated immune surveillance.…”
Section: Discussionsupporting
confidence: 82%
“…The selective loss of expression of individual HLA molecules on tumor cells has been described (13,41). In this study we have identified two cell lines (LS 174T and LS 411), in which loss of expression of HLA-A2 has occurred.…”
Section: Discussionmentioning
confidence: 86%
“…Surface expression of this complex controls the recognition of a cell by antigen-specific cytotoxic T lymphocytes (2,3) and has been implicated in the rejection of intracellular parasites (4,5), tumors (6,7), and tissue allografts (8). Loss of expression of HLA molecules has been described on a wide variety of tumor types (9)(10)(11)(12)(13) and has been argued as presenting a mechanism whereby a tumor cell can escape from immune surveillance by cytotoxic T lymphocytes (14,15). To better understand the control of HLA expression on tumor cells, we have established a DNA-based method for tissue typing the HLA-A locus by a one-step PCR from genomic DNA.…”
mentioning
confidence: 99%
“…In vitro, both CD58 and CD59 antibody alone were shown to reduce the CD2-dependent response of a murine T-cell clone expressing human CD2 (Hahn et al, 1992). It is thus conceivable that presence of CD59 on the cell surface might compensate a reduction or loss of LFA-3 (CD58) which has been reported to occur in some colorectal carcinomas (Smith et al, 1989;Koretz et al, 1991). In view of the novel functions attributed to CD55 and CD59, presence of CD55 and absence of CD59 might contribute to resistance of a tumour cell to cell-mediated cytotoxicity unrestricted and restricted, respectively, by the major histocompatibility complex (Browning & Bodmer, 1992;Moller & Hammerling, 1992).…”
Section: Discussionmentioning
confidence: 99%